Catalytic Consequences of Micropore Topology on Biomass Pyrolysis Vapors over Shape Selective Zeolites - Naqvi, S.R. (Elsevier Ltd, 2017)
Research on utilization of abundant rice residue for valuable bioenergy products is still not explored completely. A simple, robust, cheap and one step fast pyrolysis reactor is still a key demand for production of bioenergy products, i.e. high quality bio-oil and bio char. Bio-oil produced from fast pyrolysis has poor quality (e.g. acidic and highly oxygenated). Catalytic fast pyrolysis using zeolites in the fast pyrolysis process effectively reduce the oxygen content (no H2 required). In this paper, zeolites having a variety of pore size and shape (small pore: SAPO-34 (0.56), Ferriertite (20), medium pore: ZSM-5 (23), MCM-22 (20), ITQ-2 (20) and large pore zeolite Mordenite (20) were tested in a drop type fixed-bed pyrolyzer. The catalytic deoxygenation is conducted at 450°C at the catalyst/biomass ratio of 0.1. Zeolite catalysts, its pore size and shape could influence largely on deoxygenation. Small pore zeolites did not produce aromatics while medium pore zeolites formed higher amount of aromatics. ZSM-5 and ITQ-2 zeolites were especially efficient for the higher deoxygenation of biomass pyrolysis vapors due to better pore dimension and higher acidity. © 2017 The Authors.